Pengaruh Stock Selection, Market Timing Ability dan Fund Longevity Terhadap Kinerja Reksadana (Studi Kasus Pada Reksadana Saham Syariah Yang Terdaftar Di OJK Tahun 2017-2019) (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this research is to analyze the effect of the Stock Selection, Market Timing Ability and Fund Longevity of the performance of Islamic equity funds registered with the OJK in 2017-2019. To measure stock selection and market timing ability variables using the Treynor-Mazuy model. While to measure the performance of Islamic equity mutual funds using the Sharpe model. Population in this research Islamic equity funds year 2017-2019 amounted 43 company. Samples were taken by purposive sampling method and 21 Islamic equity mutual fund companies were selected that met the criteria. This research method uses multiple linier regression analysis. The results of this study indicate that stock selection and market timing ability have a significant effect on the performance of Islamic equity funds. On the other hand, fund longevity has no significant effect on the performance of Islamic equity funds. Keyword: stock selection, market timing ability, fund longevity, performance of Islamic equity funds.